Excitation power dependent population pathways and absolute quantum yields of upconversion nanoparticles in different solvents. Issue 12 (15th March 2017) - Würth, C.; Kaiser, M.; Wilhelm, S.; Grauel, B.; Hirsch, T.; Resch-Genger, U.
Abstract : This study explores radiationless deactivation pathways and absolute quantum yields of upconversion nanoparticles (UCNPs) to drive the rational design of brighter and more efficient UCNPs. Abstract : The rational design of brighter upconversion nanoparticles (UCNPs) requires a better understanding of the radiationless deactivation pathways in these materials. Here, we demonstrate the potential of excitation power density ( P )-dependent studies of upconversion (UC) luminescence intensities, slope factors, and absolute quantum yields ( Φ UC ) of popular β-NaYF4 :20% Yb 3+, 2% Er 3+ UCNPs of different surface chemistries in organic solvents, D2 O, and water as a tool to gain deeper insight into the UC mechanism including population and deactivation pathways particularly of the red emission. Our measurements, covering a P regime of three orders of magnitude, reveal a strong difference of the P -dependence of the ratio of the green and red luminescence bands ( I g/r ) in water and organic solvents and P -dependent population pathways of the different emissive energy levels of Er 3+ . In summary, we provide experimental evidence for three photon processes in UCNPs, particularly for the red emission. Moreover, we demonstrate changes in the excited population dynamics via bi- and triphotonic processes dependent on the environment, surface chemistry, and P, and validate our findings theoretically.